Short Report: Identification of Virulence-Associated Plasmids in Rhodococcus equi in Humans with and without Acquired Immunodeficiency Syndrome in Brazil - Ribeiro, Márcio Garcia [UNESP]; Takai, Shinji; de Vargas, Agueda Castagna; Mattos-Guaraldi, Ana Luiza; Ferreira Camello, Thereza Cristina; Ohno, Ryoko; Okano, Hajime; da Silva, Aristeu Vieira (Amer Soc Trop Med & Hygiene, 2011)
Virulence of Rhodococcus equi strains from 20 humans in Brazil was investigated by using a polymerase chain reaction to characterize isolates as virulent (VapA), intermediately virulent (VapB), and avirulent. Nine isolates were obtained from human immunodeficiency virus (HIV)-positive patients, six from HIV-negative patients, and five from patients of unknown status. Five isolates were VapB positive, four were VapA positive, and eleven were avirulent. Among the nine isolates from HIV-positive patients, five contained VapB plasmids and two contained VapA plasmids. Five VapB-positive isolates had the type 8 virulence plasmid. Eleven of the patients had a history of contact with livestock and/or a farm environment, and none had contact with pigs.